The Social Construction of the Soundscape of the Castilian Cities (15th and 16th Centuries) - Coronado Schwindt, Gisela Beatriz (2021)
This paper seeks to develop some conceptual elements that articulated the social construction of the soundscape of the urban spaces of the kingdom of Castile (15th–16th centuries). We focus our attention on the revision of the normative spheres that structured the subjective universe of the Castilian inhabitants, in order to notice and spot the different sound representations that intervened in the spatial and social configuration of the cities, their possible conflicts, and levels of acoustic tolerance. This proposal is part of the so-called “sensorial turn” in the Social Sciences, defined by David Howes as a cultural approach to the study of the senses as well as a sensorial approach to the study of culture. The research is carried out through the analysis of the sensory marks present in a documentary corpus made up of normative documents (municipal ordinances, books of agreement, chapter acts, diocesan synods, and royal dispositions) and judicial documents (General Archive of Simancas) combining methods of discourse analysis and the history of the senses. In the article, we argue and remark that the sound dimension operated as a device that acted in the shaping of the identity of places, since it contributed to define and delimit their use. This was reflected in the importance given by the authorities to the normative regulation of the community, which included a textual dimension in which the historical soundscape was imprinted, revealing the multiple social interactions that integrated it.